Perbandingan Uji Kuat Tekan Beton Menggunakan Agregat Kasar Pecah Manual dengan Agregat Kasar Pecah Pada Mesin - Mujur, Raftly M.; Jasman, Jasman; Hamsyah, Hamsyah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Construction requires strong and abundant materials, so various concrete mixing innovations are needed, such as the use of a variety of coarse aggregate materials. This research aims to determine the characteristics, comparison of concrete compressive strength tests and split tensile strength tests of manually broken coarse aggregate concrete with machine broken coarse aggregate using the SNI method at the Structure and Materials Laboratory of the Muhammadiyah University of Parepare. The research results show that the characteristics of manually broken and machine broken coarse aggregates meet laboratory material testing standards. The compressive strength value of manually broken coarse aggregate concrete is 24.63 Mpa and machine broken coarse aggregate concrete is 25.19 Mpa. The splitting tensile strength value of manually broken coarse aggregate concrete is 4.778 Mpa and machine broken coarse aggregate concrete is 5.444 Mpa. The use of machine-broken coarse aggregate produces higher compressive and tensile strength values for concrete compared to manually broken coarse aggregate.